Nutrients regulation of skin cells from canines and cats via Wnt/β-catenin signaling pathway - Sun, Xue; Ma, Yan; Gao, Yi; Li, Jiaxi; Li, Yunliang; Lv, Lei (Frontiers in Veterinary Science, 2025)
For pets, healthy hair not only represents their beautiful appearance, but also reflects their overall health status. Nutritional imbalance, skin parasites, and stress can all cause a large amount of hair loss in pets, leading to skin-related diseases and posing a threat to their health. So, it is very important to understand and find solutions to alleviate or treat pet hair loss. The Wnt/β-catenin signal plays a core role in the hair regeneration process. Here, we report that keratin hydrolyzed, egg yolk lecithin, and fish collagen peptide promote β-catenin nuclear translocation and significantly enhance the expression of their target genes in canines and cats skin cell lines, indicating that these nutrients are likely to play a beneficial role in promoting hair regeneration in canines and cats.